The Impact of Alcohol Use on Antiretroviral Therapy Adherence in Koreans Living with HIV - Ji Young Kim; Youngran Yang; Hyun Kyung Kim; Ji Young Kim (Elsevier, 2018)
Purpose: This study aimed to examine the impact of alcohol use on the antiretroviral therapy (ART) adherence of Koreans living with human immunodeficiency virus (HIV). Methods: A total of 144 HIV-infected Koreans older than the age of 19 years who had been receiving antiretroviral drugs for at least 3 months were surveyed. Alcohol use was identified as nonhazardous, binge, hazardous, and alcohol dependent as determined by the Alchol Use Disorder Identification Test-Korea (AUDIT-K). ART adherence was defined according to the components of adherence motivation, adherence knowledge, and 95% medication adherence using the modified Morisky scale. Collected data were analyzed using logistic regression analysis for each component of therapy adherence. Results: Of all participants, 13.9% were binge drinkers, 17.4% were hazardous drinkers, and 4.2% were alcohol dependent. For low adherence motivation, the odds ratio for the hazardous drinkers was 7.47 [95% confidence interval (CI): 1.72-32.41; p = .007] and for the alcohol dependent, it was 12.61 (95% CI: 1.38-115.38; p = .025) when compared with the nonhazardous drinkers. For medication adherence under 95%, the odds ratio for binge drinkers was 4.65 (95% CI: 1.15-18.92; p = .032), for hazardous drinkers was 8.05 (95% CI: 2.08-31.20; p = .003), and for the alcohol dependent was 27.67 (95% CI: 2.12-360.51; p = .011). Conclusion: It is recommended that Korean institutions and governments develop specific mediation and counseling programs that include alcohol use-related monitoring for the improvement of the ART adherence of people living with HIV. Keywords: acquired immunodeficiency syndrome, alcoholism, HIV, Korea, medication adherence